Hepatoses in highly productive cows, their treatment and prevention - Smolentsev Sergey; Onuchina Maria; Nikolaeva Zhanna; Goncharov Nikita; Gracheva Olga; Gasanov Alizade; Mukhutdinova Dina; Zukhrabova Zulfiyat; Karpova Natalia; Asrutdinova Rezilya (BIO Web of Conferences, 2024)
Ketone bodies in the urine of first-born heifers on the first day after calving constitute an indicator within the normal range, but by the 30th day after calving in sick animals, the reaction to ketone bodies is 8 times higher than normal. All changes indicate violations of protein and fat metabolism, as well as changes in the acid-base balance in the animal’s body, which is associated with impaired liver function and damage to this organ. In order to find the most effective method of pharmacoprophylaxis and pharmacotherapy of hepatoses and fatty liver dystrophy in the first heifers, the drug “Hepatoject”, a hepatoprotective choleretic drug, was used on the farm. To prevent liver dysfunction and treat animals with hepatosis, 100 ml of hepatoject was administered intravenously after calving for 5 days, which led to 100% preservation of animals with normalization of liver function, milk productivity, biochemical parameters of blood and urine.